Exploring legal frameworks for the capacity-building of Africa's youth for the optimization of economic integration in Africa - Moyo, Dumoluhle Mazwemzini G (Department of Commercial Law, 2025)
This study embarks on a nuanced, comprehensive and appropriate exploration of the interplay between the youth, the law and the African integration landscapes. Drawing close attention to the youth as the main stakeholders of the research, it located them within the African integration agenda, championing them as pivotal stakeholders. It did so by acknowledging and problematizing the ongoing discourse of integration—exploring goals, theories, histories and implications of integration on the continent. In advancing towards its objectives, it carried out a comparative examination of the wherewithal of African legal frameworks to leverage these pivotal stakeholders of integration. Emerging from these explorations, the work identifies, demonstrates and problematizes a rhetoric and culture of doing for the youth, not with the youth. This then set the foundation for illuminating the latent potential within the vibrant youthful demographic of the continent for the integration agenda. By doing so, it endeavours to converse and grapple with the subtle yet significant challenge of whether African integration can be sustainably progressed if the prevailing narrative depicts youth as passive recipients rather than active co-creators. Ultimately, the research is timely in exploring the indispensability of the youth, concerned with whether they will remain unrealised potential or can be maximised and leveraged to optimize African integration.